2021
DOI: 10.33899/ijvs.2020.126853.1401
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the lethal concentration 50% (LC50) of lead chloride and its accumulation in different organs of Gambusia affinis fish

Abstract: In the present research, mosquito fish Gambusia affinis have been exposed to lead chloride during 24, 48, 72 and 96 hours in order to evaluate the lead chloride lethal 50 (LC50) concentration and the Its residue in certain organs of fish. Usage of the EPA computer software based on Finney Probit Analysis method has been statistically tested for the data collected LC50 values of G. affinis if 24, 48, 72 and 96 hours were found to be 59.4, 55.9, 51.1 and 49. 0 mg/L, respectively. LC50 decreased as mean exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The particles measured less than 25 nanometers. The dose concentrations were selected in light of the Median Lethal dose 50 experiment (LD50) (10). Concentrations of 20 and 40 mg/ kg of body weight were used in this study.…”
Section: Choose the Doses Of The Studymentioning
confidence: 99%
“…The particles measured less than 25 nanometers. The dose concentrations were selected in light of the Median Lethal dose 50 experiment (LD50) (10). Concentrations of 20 and 40 mg/ kg of body weight were used in this study.…”
Section: Choose the Doses Of The Studymentioning
confidence: 99%
“…The acute oral LD50 of chlorpyrifos in chick was 13.705 mg/kg B.Wt, in the previous study the LD50 of chlorpyrifos in chicks was 18.14 mg/kg B.Wt and some reported LD50 ranged 25-35 mg/kg B.Wt (19) we can attributed this different to variation of chlorpyrifos origin, as well as the solvents, the intermediate vehicles, and the Iraqi Journal of Veterinary Sciences, Vol. 35, Supplement I, 2021 (13)(14)(15)(16)(17)(18) Proceedings of the 2nd Scientific Conference, College of Veterinary Medicine, University of Duhok concentration of the active ingredient in the formula as well as laboratory condition, and animal breed variation (20). It is worthy of mention that chlorpyrifos consider as highly toxic in birds and poultry, the toxic signs represented by cholinergic toxicity syndrome like salivation, defecation, muscle spasm, dispense and death due to a penea.…”
Section: Discussionmentioning
confidence: 99%
“…Iraqi Journal of Veterinary Sciences, Vol. 35, Supplement I, 2021 (13)(14)(15)(16)(17)(18) Proceedings of the 2nd Scientific Conference, College of Veterinary Medicine, University of Duhok Interaction of oral LD50 of metronidazole with oral LD50 of chlorpyrifos at ratio 1:0, 5 five chicks from both sex were used, firstly metronidazole dosed orally at100% of LD50 and directly dosed orally with 50% of oral LD50 of chlorpyrifos, the result read death X or life O after 24 hour, and increased or decreased in dose was constant 10% of LD50 and repeat dosing up or down for 3chicks after changing the result death to life and versa and calculate orall LD50s of metronidazole and chlorpyrifos depending upon the diagram and equation of Dixon as described above. We subjected the LD50s of both metronidazole and chlorpyrifos to isobolographic analysis also the interaction index was calculated (14,15).…”
Section: Determination Of the Oral Ld50 Of Chlorpyrifos In Chicks By Up And Down Methodsmentioning
confidence: 99%
“…The permissible limited concentration of Cu ion in Iraqi water environment is 0.05 mg/l. As pollution concentration is 0.199 mg/l, a high concentration of Cu inters the body through the digestive tract, gills, and accumulation in the tissue lead to abnormal locomotor responses and adverse pathological effects in fish and other aquatic organisms (7)(8)(9)(10). Delahaut et al (11) reported the significant effects of Cu in gill electrolytes and cause reduction in sodium ions and cause, an imbalance of osmoregulation in C. carpio and cause damage to gill, kidney, liver, and spleen architecture (12), blood lysis, and anemia in Clarias lazera, and enzyme activity disturbances (13,14).…”
Section: Introductionmentioning
confidence: 99%